Perfil soroepidemiológico e avaliação das citocinas IFN-Ɣ, TNF, IL-6 e IL-10 em indivíduos com suspeita clínica de chikungunya durante a epidemia de 2017 no Ceará - Viana, Vânia Angélica Feitosa (2020)
Arboviruses, mainly dengue, Zika and chikungunya, have been one of the major public health problems in the world. However, CHIKV infection particularly has a strong inflammatory component involving innate and adaptive immunity. Nevertheless, the immunological mechanisms present in the protection or pathogenesis are not yet fully elucidated. Thus, this study aimed to investigate the seroepidemiological profile in individuals with clinical suspicion of chikungunya; to associate serum levels of IFN-γ, TNF, IL-6 and IL-10 cytokines with the disease progression stages and seropositivity IgM and anti-CHIKV IgG. This is a descriptive cross-sectional study consisting of 393 suspected chikungunya cases that were referred to the Central Public Health Laboratory of the State of Ceará in 2017 for laboratory diagnosis. Anti-CHIKV / DENV / ZIKV IgM and IgG serologies and cytokine quantifications: IFN-γ, TNF, IL-6 and IL-10 were performed by ELISA. The epidemiological profile of this study was characterized with a predominance of cases from the city of Fortaleza, female and aged from 40 to 59.9 years. Of the total, 71.0% (279/393) had reagent IgM anti-CHIKV serology, 67.4% (265/393) reagent anti-CHIKV IgG and 57.3% (225/393) were reagent for both IgM and IgG anti-CHIKV. Of the subjects with IgM and / or IgG reactive anti-CHIK antibodies, 40.7% (138/339) were in the acute phase, 35.7% (121/339) post-acute and 23.6% (80/339) in the chronic phase. Older female participants had a longer time of symptoms of the disease, suggesting that gender and age may be contributing factors to disease chronicity. The positivity of anti-CHIKV IgM antibodies occurred from the 3rd day of symptom onset, with a larger number of cases between 6 to 8 days. Regarding the detection of anti-CHIKV IgG, there was a higher concentration of cases within 7 to 9 days of onset of symptoms reported. Persistence of anti-CHIKV IgM circulation was observed in a significant proportion of individuals with more than 90 days of symptoms (49/80). Anti-CHIKV, anti-DENV and/or anti-ZIKV IgM codetections were found in 54/393 of the samples (13.7%), with the predominance between chikungunya and dengue (45/54; 83.3%). For all titrated cytokines (IFN-γ, TNF, IL-6 and IL-10) it was found that the group acute chikungunya had statistically higher concentrations than the post-acute and chronic groups. Similarly, individuals with IgM reagent and non-reactive CHIKV IgG serology were found to have significantly higher levels of these cytokines than the other groups. When comparing the phases of CHIK progression, it was found that the serum levels of TNF and IL-10 showed a more pronounced decline in the chronic phase as compared to acute and post-acute, while IFN-γ levels decreased slightly in the post-acute phase, in contrast to an increase in the chronic phase. IL-6 levels varied weakly between the periods studied. Individuals with IgM codetection anti-CHIKV, anti-DENV, and anti-ZIKV had statistically higher levels of these cytokines compared to the single anti-CHIK detection group. These findings help to understand the mechanisms of CHIK infection immune response, being relevant for a better understanding of the immunopathology and behavior of the disease.